DESIMINASI DERITA KORBAN MUTILASI (SEBUAH KAJIAN SOSIOLOGI KOMUNIKASI) - Pribadi, Farid; Raditya, Ardhie (Universitas Wijaya Kusuma Surabaya, 2019)
This study aims to analyze the practices of symbolic violence in the news of murder cases accompanied by mutilation in Blitar District. This interest in discussing the phenomenon of reporting is due to the researchers' concern about the phenomenon of 'taught violence' committed by journalists. The practice of violence that is taught is characterized by the style of disclosure of facts about events in an open and massive manner. The research method used is a qualitative method. The data analysis technique is using Robert Entman's framing analysis model. The subject of this research is online mass media www.tribunnews.com. The reason for choosing this research subject is based on the ranking of the number of visitors or online mass media visitors namely www.alexa.com stating that www.tribunnews.com ranks first most visitors as of April 2019. The results of this study are that www.tribunnews.com has done the practice of symbolic violence. This practice is characterized by the style of the arrangement of words that seem dramatic, systematic, accompanied by pictures of the condition of the victim and the victim's family tend to be terrible and repetitive. In addition, photographs and daily lives of victims during their life were also revealed in detail. The condition of the house and family during grieving is also told dramatically. Regarding the profile of the perpetrators of the killings, they received a dominant portion of the reporting. The style of disclosing the fact of the murder incident relies more on news sources from the police. While the performance of journalists who can be expected such as supporting data on the profile of perpetrators to help disclose cases tends to be avoided.Â Keywords: Mutilation, Frame Analysis, Symbolic Violence